A Valence‐Engineered Self‐Cascading Antioxidant Nanozyme for the Therapy of Inflammatory Bowel Disease. Issue 27 (5th May 2022) - Wang, Quan; Cheng, Chaoqun; Zhao, Sheng; Liu, Quanyi; Zhang, Yihong; Liu, Wanling; Zhao, Xiaozhi; Zhang, He; Pu, Jun; Zhang, Shuo; Zhang, Huigang; Du, Yan; et al.
Abstract: Antioxidant treatment strategy by scavenging reactive oxygen species (ROS) is a highly effective disease treatment option. Nanozymes with multiple antioxidant activities can cope with the diverse ROS environment. However, lack of design strategies and limitation of negative correlation for nanozymes with multiple antioxidant activities hindered their development. To overcome these difficulties, here we used ZnMn2 O4 as a model to explore the role of Mn valency at the octahedral site via a valence‐engineered strategy, and found that its multiple antioxidant activities are positively correlated with the content of Mn 4+ . Therefore, through this strategy, a self‐cascading antioxidant nanozyme LiMn2 O4 was constructed, and its efficacy was verified at the cellular level and in an inflammatory bowel disease model. This work not only provides guidance for the design of multiple antioxidant nanozymes, but also broadens the biomedical application potential of multiple antioxidant nanozymes. Abstract : A valence‐engineered strategy to develop self‐cascading nanozymes with simultaneous multiple antioxidant activities has been proposed. Nanozyme LiMn2 O4 (LM), as the final optimized material, exhibits the best SOD‐like, CAT‐like, GPx‐like, and hydroxyl radical scavenging activities. The outstanding antioxidant capacity of LM was demonstrated at the cellular level and in the treatment of inflammatory bowel disease in mice.